Pengaruh Pendidikan Terhadap Pola Pikir Anak di Desa Kalirejo Kecamatan Kraton Kabupaten Pasuruan - Izza Afkarina; Sugeng Pradikto (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Education is an important element in developing children's minds, especially in rural areas where education is often not a priority. The aim of this research is to analyze the impact of education on the way children think in Kalirejo Village, Kraton District, Pasuruan Regency. The method used was a quantitative design with a survey approach, with 22 randomly selected respondents. Information is obtained through surveys that assess educational variables and children's thinking patterns. The results show that the applied regression model shows satisfactory performance, with an R Square value of 0.634, which means that education can explain around 63.4% of the variation in children's thinking patterns. The t test results show that education has a significant influence on children's thinking patterns, with a significance value of 0.000. The impact of this research is the importance of increasing access and quality of education in rural areas, as well as the need for policies that encourage public awareness of the role of education in children's future. It is hoped that this research can become a reference for the government and related parties in designing more effective education strategies.